Pengaruh Penerapan Sistem Akuntansi Keuangan Daerah Terhadap Kualitas Laporan Keuangan ( Studi Kasus: Pemerintah Daerah Kabupaten Pulau Morotai ) - Umar, Ardin; Hasan, Jamiludin (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This research is explanatory research, explanatory research is a research method that intends to develop the clarity of phenomena that occur at a source and seeks to get answers to the causal relathionship between variables trough hypothesis testing. Where the independent variable in the study is the regional financial accounting system and the dependent is the quality of financial reports. From the table above, it can be seen that the education level of the respondents with the highest number of respondents was the bachelor’s level of education with 44 respondents or 61.1% D3 level with 15 respondents or 20.8% high school level as many as 8 respondents or 11.1% and masters level as many as 5 respondents or 6.9% this study aims to determine the effect of implementing regional financial accounting system on the quality of financial reports in the district governmentof morotai island district. Regional finances are proven to have a positif influence on the quality of financial reports in the local government of morotai island district, this is evidenced by a comparison of the calculated t values and t table values where the t calculated obtained is greater than the t table that has been determined